Photosensitization of Colloidal SnO2 Semiconductor Nanoparticles with Xanthene Dyes - N. Nagarajan; G. Paramaguru; G. Vanitha; R. Renganathan (Journal of Chemistry)
The photochemical behavior of xanthene dyes (fluorescein, erythrosine, and eosin) with colloidal SnO2 nanoparticles was probed by UV-visible, steady state, and time resolved fluorescence measurements. The prepared SnO2 nanoparticles were characterized by using UV-visible and powder XRD measurements. The xanthene dyes were adsorbed on the surface of colloidal SnO2 nanoparticles through electrostatic interaction. Apparent association constant (Kapp) was calculated from the relevant fluorescence data. The larger value of apparent association constant indicates a strong association between xanthene dyes and SnO2 nanoparticles. The fluorescence quenching is mainly attributed to electron transfer from the excited state xanthenes to the conduction band of colloidal SnO2. The electron transfer mechanism was explained based on the Rehm-Weller equation as well as the energy level diagram.